Pemanfaatan Media Sosial Untuk Mempromosikan Usaha Rumah Tangga Kedai Ken Al - Ariyansyah, Ardika Okta; Susena, Karona Cahya (Universitas Dehasen Bengkulu, 2024)
Media Sosial is an internet-based application that allows consumers to access various information, opinions, and experiences. It can meet consumer needs by providing factual, specific, and non-commercial information. In the digital era, media sosial has become a crucial marketing platform for businesses. It helps in promoting products, increasing customer engagement, and reducing costs. Kedai Ken Al, a Nusantara-based restaurant, uses social media platforms like Instagram, Facebook, and WhatsApp to reach a wider audience and increase sales. Digital marketing is a strategy to promote products, engage with customers, reduce costs, and conduct online sales. Promoting products is a priority for businesses to inform consumers about their products and services, and it helps them understand consumer needs and meet their needs. The activity is to identify the level of knowledge and skill level regarding social media in a responsible manner between the trainer and companion and the participants. Participants are given training and mentoring in community service and assistance regarding digital marketing, especially through social media. Continuing Training and Mentoring in service and mentoring through materials: creating an account for a business, uploading product photos, editing photos using features from Facebook and Instagram, and providing responses to consumers. Marketing activities are still considered traditional, involving small products or what is commonly known as stalls. The promotional method used is still considered to rely on word of mouth (WOM) promotion or what is better known as word of mouth promotion. Promotion aims to convey information related to a product or brand to the target market in order to attract their attention and influence their attitudes. This assistance is carried out by providing knowledge that one of the promotions that can be carried out is social media such as Instagram, WhatsApp, Facebook and TikTok. The use of social media as a tool for business promotion makes it the right choice because, apart from that, social media users are increasing day by day. Interactivity in social media is also a high form of communication with other social media users. Instagram is a platform for sharing photos and videos, applying digital filters, and sharing visual information on Instagram. WhatsApp proves the use of marketing on WhatsApp as an effective business promotion tool because it can be accessed by anyone, so that the promotional network can be wider on Jalan Kini Balu 4, Kebun Tebeng sub-district. WhatsApp does not use credit and internet data.